The payment system and bank modernization project = (The World Bank in Vietnam (WB), 2004)
The ultimate objective of the Bank System Modernization Project is to assist in the development of a modern banking sector able to service the needs of a growing economy, thereby increasing confidence in the Vietnamese banking system. The immediate objectives of the project are to: 1) improve payment services in the economy in order to reduce float, speed up circulation of funds and increase efficiency of funds transmission, while providing convenience and service to users; and 2) strengthen the institutional capabilities of participating banks in order to stimulate commercial bank initiatives to improve internal management and customer service. The project consists of four components: 1) a national inter-bank payment clearing and settlement system; 2) commercial banks' intra-bank payment systems; 3) commercial banks' institutional strengthening; and 4) project management support.